Financial planning as a policy tool in the petroleum industry (the case study: ojsc "Surgutneftegas") - Romanyuk V. B. Vera Borisovna; Karyakina A. Anna; Vershkova E. M. Elena Mikhailovna; Grinkevish L. Larisa; Pozdeeva G. P. Galina Petrovna (Petroleum Engineering Economics and Mining Law, 2016)
Title screen